Building the future - London TV Service ([Derry, New Hampshire] : Chip Taylor Communications, 2002)
This program examines the cutting-edge achievements being made in the green technology revolution and explores the pioneering work now being developed to help society strike a practical balance between exploitation and conservation to create the sustainable city of the future
Title from title screen
DVD format
Keywords: Cities and towns; Sustainable development; Green technology